Medical student’s perceptions of different teaching aids from a tertiary care teaching institution - Bagga, Inderjit Singh; Goyal, Vipin; Singh, Abhishek; Chawla, Hitesh; Goel, Shewtank; Goyal, Pooja (International Journal of Research in Medical Sciences, 2017)
Background: In recent years there has been increasing interest and growing concern regarding the role of learning environment in undergraduate medical education. Student’s feedback can play vital role in this regard. Aim of the study was conducted to access student’s perception of different teaching aids in a medical college, with an aim to improve their use in didactic lectures. Methods: In this cross-sectional study, all the medical undergraduate students currently studying in the second year were included in this study. A self-administered questionnaire served as study tool. The study population consisted of undergraduate medical students (MBBS) who were currently posted in the Department of Forensic Medicine for theory and practical classes. Questionnaire was handed out to 86 students. The inventory consisted of 25 items and each item scored on a five-point likert scale. Results: Out of 86, 80 returned the completely filled questionnaires. 62 (77.5%) out of 80 had their schooling in English medium and the visual aid predominantly used in the schools. Study subjects preferred a combination of audio-visual aids during a didactic lecture. Blackboard teaching was preferred in the following areas: Facilitated interaction between student and teacher, Aroused interest in learning, Helped to hold attention in class, More helpful to grasp the content, Better able to cope with teaching speed of teacher, More useful in small group, Increased ability to think and understand. Conclusions: Student’s preferences and feedback need to be taken into consideration when using multimedia modalities to present lectures to students. Feasible student suggestions must be implemented for further improving the use of audio-visual aids during didactic lectures to make teaching learning environment better.